Csp2-H/F bond activation and borylation with iron - Zars, Ethan; Pick, Lisa; Kankanamge, Achala; Gau, Michael R.; Meyer, Karsten; Mindiola, Daniel J. (Chemical Communications, 2024)
Reduction of [K2(tBupyrr2pyr)Fe2(μ-N2)] (1) with two equiv. of KC8 in the presence of crown-ether 18-C-6 yields the N2 adduct [K(18-C-6)2(tBupyrr2pyr)Fe(N2)] (2). Complex 2 heterolytically splits the Csp2-H bond of benzene to form [K(18-C-6)(tBupyrr2pyr)Fe(C6H5)] (3), whereby usage of a diboron B2pin2 promotes hydride elimination to form the salt [K(18-C-6)HB2Pin2] (4). Similarly, 3 can also be formed by cleavage of the C-F bond of fluorobenzene. Reaction of 3 with ClBcat yields [K(18-C-6)(thf)2][(tBupyrr2pyr)FeCl] (5) and PhBcat and the former can be reduced to 2 to complete a synthetic cycle for heterolytic benzene C-H activation and borylation.
CRIS-Team Scopus Importer:2024-11-29

Divergent Reactivity of Azides and Diazoalkanes Toward Ferrous Complexes and Isolation of a FeIII Carbene Radical Complex - Zars, Ethan; Pick, Lisa; Kankanamge, Achala; Gau, Michael R.; Carroll, Patrick J.; MacMillan, Samantha N.; Lancaster, Kyle M.; Meyer, Karsten; Mindiola, Daniel J. (Organometallics, 2025)
Treatment of [(tBupyrr2pyr)Fe(OEt2)] (1-OEt2) (tBupyrr2pyr2- = 3,5-tBu2-bis(pyrrolyl)pyridine) with trimethylsilyl azide (N3SiMe3) and subsequent photolysis at 390 nm results in clean formation of [(tBupyrrpyrpyrrNHSiMe3)Fe] (2) as the result of a nitrene being inserted into a tert-butyl C-H bond of the tBupyrr2pyr ligand. Treatment of 1-OEt2 with azidotrimethyltin (N3SnMe3), however, results in isolation of the γ-bound azide adduct ferrous complex, [(tBupyrr2pyr)Fe(N3SnMe3)] (1-N3SnMe3). When treated with diphenyl diazomethane (Ph2CN2), complex 1-OEt2 converts to the iron carbene complex [(tBupyrr2pyr)FeCPh2] (1-CPh2), and the X-ray structure revealed a Fe-CPh2 bond length of 1.964(3) Å. A room temperature magnetic moment of 1-CPh2 indicates an S = 2 spin state, consistent with a high-spin FeIII center antiferromagnetically coupled to a carbene radical anion (CPh2•-). Zero-field 57Fe Mössbauer spectroscopy and Fe K-edge X-ray absorption spectroscopy confirm this assignment. In solution, complex 1-CPh2 rearranges to [tBupyrrpyrC(═CPh2)-C(CMe3)═CH-C(CMe3)═NFe]2 (3) resulting from carbene insertion into the 1-position of the pyrrolide arm of the tBupyrr2pyr ligand and dimerization. Complex 3 possesses two high-spin FeII centers according to 57Fe Mössbauer spectroscopy, with antiferromagnetic coupling between the spin centers. Monitoring the conversion of 1-CPh2 to 3 by UV-vis spectroscopy reveals this process to be first order in 1-CPh2 with a highly ordered transition state evidenced by activation parameters: ΔS‡ = −87.6 ± 25.8 J·mol-1·K-1 and ΔH‡ = 63.1 ± 8.3 kJ·mol-1.
CRIS-Team Scopus Importer:2025-01-31

Flash Communication: Rearrangement of a tris-Carbene Ligand Precursor to an all-N-Bound tris-Imidazole Iron Complex: Flipping the Umbrella - Hartmann, Tom; Pick, Lisa; Heinemann, Frank Wilhelm; Scheurer, Andreas; Meyer, Karsten (Organometallics, 2025)
Treatment of the ligand precursor H3TIMMNMesCl3 (TIMMNMes = tris-[(3-mesityl-imidazol-2-ylidene)methyl]amine) with an excess of base yields the literature-known ferrous tris-N-heterocyclic carbene (NHC) complex [(TIMMNMes)FeIICl]Cl (1-Cl). In contrast, utilizing a substoichiometric amount of base initiates a unique rearrangement of all three NHC pendant arms to yield the tripodal, all-N-bound tris-imidazole [(N-TIMMNMes)FeIICl]Cl (2-Clsol). Divalent 2-Cl and 2-PF6 are fully characterized, structurally by single-crystal X-ray diffraction analysis and spectroscopically by 1H NMR and 57Fe Mössbauer spectroscopy as well as SQUID magnetization measurements, to demonstrate the influence of the change from a soft strong-field to a hard weak-field ligand. Optimized reaction conditions for the reproducible, high-yield carbene-to-imidazole rearrangement were developed in a series of experiments.
CRIS-Team Scopus Importer:2025-01-31

Iron-Catalyzed Intermolecular C−H Amination Assisted by an Isolated Iron-Imido Radical Intermediate - Zars, Ethan; Pick, Lisa; Swain, Abinash; Bhunia, Mrinal; Carroll, Patrick J.; Munz, Dominik; Meyer, Karsten; Mindiola, Daniel J. (Angewandte Chemie International Edition, 2023)
Here we report the use of a base metal complex [(tBupyrpyrr2)Fe(OEt2)] (1-OEt2) (tBupyrpyrr22−=3,5-tBu2-bis(pyrrolyl)pyridine) as a catalyst for intermolecular amination of Csp3−H bonds of 9,10-dihydroanthracene (2 a) using 2,4,6-trimethyl phenyl azide (3 a) as the nitrene source. The reaction is complete within one hour at 80 °C using as low as 2 mol % 1-OEt2 with control in selectivity for single C−H amination versus double C−H amination. Catalytic C−H amination reactions can be extended to other substrates such as cyclohexadiene and xanthene derivatives and can tolerate a variety of aryl azides having methyl groups in both ortho positions. Under stoichiometric conditions the imido radical species [(tBupyrpyrr2)Fe=N(2,6-Me2-4-tBu-C6H2)] (1-imido) can be isolated in 56 % yield, and spectroscopic, magnetometric, and computational studies confirmed it to be an S = 1 FeIV complex. Complex 1-imido reacts with 2 a to produce the ferrous aniline adduct [(tBupyrpyrr2)FeNH(2,6-Me2-4-tBu-C6H2)(C14H11)] (1-aniline) in 45 % yield. Lastly, it was found that complexes 1-imido and 1-aniline are both competent intermediates in catalytic intermolecular C−H amination.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Amination; C−H Activation; Imido; Insertion; Nitrene